Malaysia – Thailand Relation in the Security Perspective - Yusof, Asyraf; Jaes, Lutfan (Journal of Social Transformation and Regional Development, 2020)
Malaysia and Thailand shared long relations history journeys for both countries. The relation between both countries can be traced back to the early 15th Century when the empire of Malacca and Ayutthaya competed to become the greatest empire in the South East Asian. In this paper, Malaysia and Thailand's relationships were explained, including both countries' security interests.   Furthermore, this paper explained Malaysia and Thailand relationships in three phases. These three phases were described from the early 15th Century until the 21st Century. Notably, Malaysia and Thailand were observed had taken a different approach in addressing their security interest.